Tonsillectomy in children with PFAPA-syndrome and Epstein-Barr viral infection - Levytska, S. A.; Gozhenko, A. I. (Journal of Education, Health and Sport, 2017)
The rates of the PFAPA-syndrome as well as the rate of the Epstein-Barr viral infection were estimated in children undergoing the tonsillectomy because of frequent episodes of tonsillopharyngitis. The streptococci origin of the disease was indicated 36% of patients, the frequency of the PFAPA-syndrome diagnosing was 3,3%. The removal of tonsils was effective method of treatment for children with chronic tonsillitis and Epstein-Barr virus infection, and children with PFAPA-syndrome.